2014
DOI: 10.1016/j.brat.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief mindfulness intervention on negative affect and urge to drink among college student drinkers

Abstract: Several theories have proposed that negative affect (NA) plays a large role in the maintenance of substance use behaviors - a phenomenon supported in laboratory-based and clinical studies. It has been demonstrated that mindfulness meditation can improve the regulation of NA, suggesting that mindfulness may be very beneficial in treating problematic substance use behavior. The current study tested whether a brief mindfulness meditation would lower levels of NA, increase willingness to experience NA, lower urges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 63 publications
2
74
0
3
Order By: Relevance
“…Data presented in the current paper were collected from a larger study ( n = 207) examining the impact of a mood induction procedure following a brief mindfulness intervention on affect and urge to drink in at-risk college student drinkers (data from all 207 participants are used in the current analyses; see Vinci et al (2014) for details of full study). The primary outcome study presented findings on the differential effects of each intervention type on the stated outcomes following a mood induction procedure, and did not examine how trait impulsivity interacted with intervention type.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data presented in the current paper were collected from a larger study ( n = 207) examining the impact of a mood induction procedure following a brief mindfulness intervention on affect and urge to drink in at-risk college student drinkers (data from all 207 participants are used in the current analyses; see Vinci et al (2014) for details of full study). The primary outcome study presented findings on the differential effects of each intervention type on the stated outcomes following a mood induction procedure, and did not examine how trait impulsivity interacted with intervention type.…”
Section: Methodsmentioning
confidence: 99%
“…They were asked to do this with an attitude of acceptance and nonjudgment. A tape recording utilized by Adams et al (2013) was used in the present study (for a written transcript of these instructions, please see Vinci et al (2014)). Results from both Adams et al (2013) and Vinci et al (2014) demonstrated that participants who were guided through the mindfulness meditation significantly increased in state levels of mindfulness when compared to the groups that did not listen to the tape.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations